Women’s speech, a call for economic empowerment: An appraisal analysis - Adisti, Aprilian Ria; Hasbi, Muhammad (Universitas Islam Negeri Ar-Raniry, 2022)
The phenomenon of women participation in entrepreneurship sector is rising significantly during the last decade. In reality, women still face many barriers in entrepreneurship both professionally and personally. In 29 August 2019, Najwa Shihab delivered an inspiring keynote speech in Global Conference on Women and Entrepreneurship held by Alibaba and Lazada in Jakarta. Since Najwa Shihab's speech got many responses from the audiences, it is highly considerable to investigate the content of the speech from a linguistic point of view. This study aimed at analyzing the spoken text from Najwa Shihab’s speech through Critical Discourse Analysis (CDA). For specific investigation, Appraisal framework was used in this study. The study focused on the attitude which relates to the feelings, emotion, reactions, and judgments of behaviour on Najwa Shihab’s speech about women and entrepreneurship. The design of the study was descriptive qualitative. The findings showed that the speech used 55 clauses which consisted of 27 clauses of affect (49%), 18 clauses of judgment (33%), and 10 clauses of appreciation (18%). All clause-complexes had attitudes. The use of affect dominated the percentage of attitudes. Furthermore, this speech also encouraged women to do 3 things: dare to change the paradigm of clichés and stereotypes into strength, dare to take a role in the national and global economy to ensure that women's voices and perspectives are present in every discussion and decision making, and support each other and bring the community that can empower other women.